Pengaruh Kemudahan Transaksi dan Kepercayaan Konsumen terhadap Penggunaan GoPay untuk Meningkatkan Transaksi Perilaku Konsumtif Mahasiswa - Nenden Susilowati; Nanda Safitri; Anggun Pinesti Priyanto; Viona Kusuma Pratiwi; Evelyna Puteri Rinaldo (AKUNTANSI 45, 2025)
The use of digital wallet services such as GoPay is increasing among students, especially college students. Ease of transactions and consumer trust are important factors in supporting GoPay use, but they have the potential to trigger consumptive behavior. The purpose of this study was to analyze the influence of ease of transactions and consumer trust on GoPay use and their impact on student consumptive behavior. The quantitative research method used was to collect primary data through questionnaires completed by 111 respondents from Economics Education students of the Faculty of Economics and Business, Yogyakarta State University (FEB UNY) who actively use GoPay. Purposive sampling and multiple regression analysis were used for data processing. Based on the analysis results, the study shows that ease of transactions has a positive and significant influence in encouraging GoPay use. Consumer trust also contributes positively and significantly to the intensity of GoPay use. Furthermore, GoPay use has positive and significant implications for the emergence of consumptive behavior among students. Simultaneously, both main factors, namely ease of transactions and consumer trust, were proven to have a significant influence on increasing GoPay use. This study illustrates that factors of convenience and trust need to be considered in the development of digital services to manage the risk of consumptive behavior among students.